Go for gigabit? First evidence on economic benefits of (ultra-)fast broadband technologies in Europe - Wolfgang Briglauer; Klaus Gugler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
The literature on the effects of telecommunications infrastructure investments find positive macroeconomic effects, however, it is severely constrained because it could hitherto only analyze investment up to "basic" broadband but not up to the newer generations of "fast" and "ultra-fast" broadband; in particular there is no such evidence available at the EU level so far. Utilizing a comprehensive panel dataset of EU27 member states for the period from 2003-2015, we estimate a small but significant effect of fiber-based ultra-fast broadband over and above the effects of basic broadband on GDP. Adoption of hybrid-fiber fast broadband is incrementally to basic broadband insignificant. Our cost-benefit analysis implies that policy intervention - as foreseen by the European Commission in its public policy targets - is only justified for coverage and adoption levels of around 50% of fast or ultra-fast broadband, whereas for 100% coverage levels we find net losses to society. Thus, it appears that - for the time being and according to the policy principle of "technological neutrality" - a combination of basic broadband, fast and ultra-fast broadband entails the largest economic net benefits to society.
Keywords: O47; L96; 330; new broadband networks; broadband speed; economic growth; EU-panel data